Ebronucimab in Chinese patients with hypercholesterolemia---A randomized double-blind placebo-controlled phase 3 trial to evaluate the efficacy and safety of ebronucimab - Yanyan Zhang; Zhaohui Pei; Beijian Chen; Yanling Qu; Xiaolin Dong; Binge Yu; Guoqin Wang; Fang Xu; Dongmei Lu; Zhimei He; Benchao Chen; Lei Ma; et al. (Elsevier, 2024)
Randomized clinical trials (RCTs) of PCSK9 monoclonal antibody(mAb) specifically for Chinese patients have been limited. This multi-center RCT is to clarify the efficacy and safety of a novel mAb, Ebronucimab, in Chinese patients. Patients diagnosed with primary hypercholesterolemia, including Heterozygous Familial Hypercholesterolemia, or mixed dyslipidemia, were categorized by ASCVD risk and randomly assigned at a ratio of 2:1:2:1 to receive Ebronucimab 450 mg or matching placebo every 4 weeks (Q4W), or Ebronucimab 150 mg or matching placebo every 2 weeks (Q2W). The primary outcome was the percentage change of LDL-C from baseline to week 12 for all groups. The least squares mean reduction difference (95 %CI) in LDL-C from baseline to week 12 of Ebronucimab 450 mg Q4W and Ebronucimab 150 mg Q2W groups versus the placebo group was −59.13 (-64.103, −54.153) (Adjusted p<0.0001) and −60.43 (-65.450, −55.416) (Adjusted p<0.0001), respectively. Meanwhile, the Ebronucimab group exhibited notably high rates in reaching LDL-C goals of each cardiovascular risk stratification. In addition, Ebronucimab effectively improved other lipid panel. During the double-blind treatment period, relatively frequently reported adverse events (AEs) were injection site reactions (ISR), urinary tract infection, and hyperuricemia (Incidence rate are 6.9 %, 4.8 % and 3.5 %). Among treatment-associated AEs, only injection site reactions (ISR) occurred more in the dose groups. In conclusion, Ebronucimab, with either 450 mg Q4W or 150 mg Q2W doses, demonstrated significant efficacy in lowering serum LDL-C level with a favorable safety and immunogenicity profile among hypercholesterolemic patients.